1997
DOI: 10.1080/01635589709514554
|View full text |Cite
|
Sign up to set email alerts
|

Intervention of transplantable human mammary carcinoma MX‐1 chemotherapy with dietary menhaden oil in athymic mice: Increased therapeutic effects and decreased toxicity of cyclophosphamide

Abstract: We investigated the effects of dietary menhaden oil on cyclophosphamide (CP) antineoplastic activity and its protective effect against CP toxicity. We found that dietary menhaden oil (HMO, 20% menhaden oil + 5% corn oil) enhanced the CP antitumor effect at the lowest dose tested (50 mg/kg) compared with the control group (LCO, 5% corn oil). Dietary HMO and CP treatment had a significant effect on the activities of tumor and liver microsomal cytochrome P-450 (CYP) over the controls. Activity of one of the key C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…(c) The suppression in cancer growth is eliminated by antioxidants, and this elimination is proportional to the inhibition of lipid peroxidation products by antioxidants (18, 24-26, 28, 29, 33, 35, 36). (d) Although therapeutic mechanisms are not always relevant to etiology, marine n-3 fatty acids have been shown to enhance the cancer-killing effect of several chemotherapeutic drugs, and this is thought to be achieved through increased lipid peroxidation or lipid peroxidation -related mechanisms (37,(39)(40)(41)(42)(43)(44)(45). We also have supporting evidence in humans implicating the peroxidation products of marine n-3 fatty acids as the proximal anticarcinogens (46).…”
Section: Evaluation Of the Experimental Evidence In Breast Carcinogenmentioning
confidence: 55%
“…(c) The suppression in cancer growth is eliminated by antioxidants, and this elimination is proportional to the inhibition of lipid peroxidation products by antioxidants (18, 24-26, 28, 29, 33, 35, 36). (d) Although therapeutic mechanisms are not always relevant to etiology, marine n-3 fatty acids have been shown to enhance the cancer-killing effect of several chemotherapeutic drugs, and this is thought to be achieved through increased lipid peroxidation or lipid peroxidation -related mechanisms (37,(39)(40)(41)(42)(43)(44)(45). We also have supporting evidence in humans implicating the peroxidation products of marine n-3 fatty acids as the proximal anticarcinogens (46).…”
Section: Evaluation Of the Experimental Evidence In Breast Carcinogenmentioning
confidence: 55%
“…We have reported that supplementing the diet of mice with fish oil increased the efficacy of edelfosine against MDA-MB 231 human breast cancer (Hardman et al, 1997), doxorubicin against A549 human lung cancer (Hardman et al, 2000) and CPT-11 against MCF-7 human breast cancer (Hardman et al, 1999a). Other investigators have found that supplementing the diet with omega-3 fatty acids increased the efficacy of: epirubicin against rat mammary tumours (Germain et al, 1999) and cyclophosphamide (Shao et al, 1997) or mitomycin (Shao et al, 1995) against MX-1 human mammary tumours. The results of in vitro studies have shown that a small amount of either eicosapentaenoic acid (EPA) or of docosahexaenoic acid (DHA), the major long chain polyunsaturated fatty acids (PUFAs) found in fish oil, added to cell culture media can cause tumour cell death but not kill cultured normal cells (de Vries and Van Noorden, 1992).…”
Section: Incell Aafamentioning
confidence: 90%
“…The results of in vitro studies have shown that a small amount of either eicosapentaenoic acid (EPA) or of docosahexaenoic acid (DHA), the major long chain polyunsaturated fatty acids (PUFAs) found in fish oil, added to cell culture media can cause tumour cell death but not kill cultured normal cells (de Vries and Van Noorden, 1992). Other reported benefits of omega-3 PUFA dietary supplements given prior to or during cancer therapy include: reversing tumour cell drug resistance (Das et al, 1998), reducing the gastrointestinal, haematological or cardiac side effects of various chemotherapeutic treatments (Hardman et al, 1999a;Germain et al, 1999;Shao et al, 1997), decreasing cancer cachexia (Karmali, 1996;Tisdale, 1993;Barber et al, 1999), and protection from alopecia (Takahata et al, 1999). Thus supplementing the diet with omega-3 fatty acids may be beneficial during cancer chemotherapy.…”
Section: Incell Aafamentioning
confidence: 99%
“…Using cultured breast cancer cell lines, it was reported that pre-enrichment of these cells with DHA enhanced their sensitivity to a variety of anti-cancer classes of drugs (Begin et al, 1986;Menendez et al, 2005;Wang et al, 2007) and more specifically to anthracyclines, an oxidative stressinducing anti-cancer drug with a quinone structure (Germain et al, 1998;Mahéo et al, 2005). Furthermore, a prolonged (several weeks) supplementation with DHA (fish oil or algae-derived DHA), initiated before and continued during chemotherapy, consistently increased the sensitivity of autochthonous mammary tumours to anti-cancer drugs (Shao et al, 1997;Hardman et al, 2001;Colas et al, 2005Colas et al, , 2006. Similar results have been observed with radiation therapy (Colas et al, 2004).…”
mentioning
confidence: 99%